Pengelolaan Sampah, Partisipasi, partisipasi ibu rumah tangga dalam pengelolaan sampah di kelurahan babakan sari kecamatan kiaracondong kota bandung: partisipasi ibu rumah tangga dalam pengelolaan sampah - Al Ghifary, Ghazy Fithrah; Hani, Umi (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2024)
This research is entitled "Housewives' Participation in Waste Management in Babakan Sari Village, Kiaracondong District, Bandung City". Babakan Sari Village is one of the sub-districts in Kiaracondong District with a land area of ​​88.1 Ha, and is a fairly densely populated sub-district, with a density of 44,516 people. Population density in an area causes the population to produce waste to increase in that area, household waste is one of the largest waste suppliers in the city of Bandung. The condition of waste accumulation which continues to increase every day requires that various other actions need to be taken immediately, considering that the amount of waste that is not balanced with existing waste management will cause pollution and also environmental damage, therefore the Bandung city government requires every area where people live to can manage their own waste before it is thrown to the TPS, the Government requires every sub-district to have waste management such as waste banks, maggot houses, and other waste management. Community participation is very necessary in waste management because the community will play an active role in waste management which is required by the Bandung City government. Housewives are the main actors in waste management in the household sector because housewives know more about the waste in the environment and can play an active role in waste management. Considering that there are still many housewives who do not manage waste in their homes, this is a problem for the Bandung City government. This research uses qualitative research methods and informant selection techniques purposive sampling, using data collection (1) Observation, (2) In-depth interviews and (3) Document study. The number of informants, namely key informants consisting of 5 housewives, and secondary informants consisting of 2 people, namely the Village and the Waste Bank. As a result of this research, researchers found information regarding the participation of housewives in managing waste. There are external and internal supporting factors for the participation of housewives in waste management, such as the existence of community associations that care about the environment, support from related community institutions, and perceived reciprocity such as getting savings in managing waste at the Waste Bank, apart from that there are also factors Internal and external barriers felt by housewives in managing waste include inhibiting factors arising from the family, and the lack of initiators in waste management.